Unrivalled insight into potential biopharmaceutical application of Allardia tridactylites (Kar. & Kir.) Sch. Bip.: Chemodiversity, in vitro bioactivities and computational analysis. (June 2023) - Tousif, Muhammad Imran; Nazir, Mamona; Riaz, Naheed; Saleem, Muhammad; Mahmood, Main Habib Ur Rehman; Ahsan, Muhammad; Tauseef, Saba; Shafiq, Nusrat; Moveed, Aniqa; Zengin, Gokhan; Korpayev, Serdar; Abbas, Zaheer; et al.
Abstract: This research work offers unrivalled insight into the chemodiversity, antioxidant and enzyme inhibition activities of Allardia tridactylites substantiated by computational analysis. Flowers and leaves of A. tridactylites were extracted separately with hexane, chloroform, ethyl acetate and ethanol to prepare four extracts of each part. Highest antioxidant potential for the ATFA and ATFLA fractions was observed in the CUPRAC (cupric ion reducing antioxidant capacity) assay as 115.57 ± 1.16 and 112.79 ± 1.8 mg of trolox equivalents per gram of the extract (mg TE/g extract) respectively, followed by chloroform and ethyl acetate extracts of the leaves and the flowers. In tyrosinase inhibition assay, the ATFE was found most active (28.92 ± 1.42 mg of Kojic acid equivalents per gram of the extract (mg KAE/g extract), while against α-amylase and α-glucosidase, the ATLC (0.63 ± 0.02 mmol of acarbose equivalents per gram of the extract (mmol ACAE/g extract) and ATFH (1.10 ± 0.01 mmol ACAE/g) were the most active respectively. Overall, ATLA and ATFA were rich in phenolics and flavonoids and also exhibited higher antioxidant activities, while in enzyme inhibition assay, the low polar extracts were more active. UHPLC-MS analysis of crude ethanolic extract result in identification of 125 secondary metabolites of various classes. The findings from various multidirectional investigations indicated that this plant held significant importance for the biopharmaceutical industries, as it served as a valuable source for the development of multiple formulations that were effective in targeting major biological enzymes. Graphical Abstract: ga1 Highlights: The current study has provided a multidimensional insight into A. tridactylites . The chemical composition of A. tridactylites was analyzed by UHPLCMS analysis. The extracts were subjected to invitro assays to assess their biological properties. Insilico studies were conducted to further validate the bioactivities of A. tridactylites.